(untitled) (Innovate Conferences, 2025)
This article explores the transformation of sociocultural identity in the context of neoglobalization. Special attention is given to the contradictory nature of global integration and cultural fragmentation, as well as the phenomenon of "redefining" identity in the digital age. The work emphasizes the importance of preserving cultural diversity amid the homogenizing tendencies of global space.